O sentimento de avulsão em o amor dos homens avulsos, de Victor Heringer e terra avulsa, de Altair Martins - Modesto, Edcleberton de Andrade (2020)
MODESTO, Edcleberton de Andrade. The feeling of avulsion in O amor dos homens avulsos, by Victor Heringer and Terra Avulsa, by Altair Martins. 2020. 104 f. Thesis (Masters degree in Languages – Literary Theory) - School of Humanities – Postgraduate Program in Literature, Pontifical Catholic University of Rio Grande do Sul, Porto Alegre, 2020. In odd times, referring to the affective life of the fictional character is an act of pilgrimage through the sentimental subjectivity of the Self. That subject appropriates the most ineffable that exists in human being: feelings. Thus, it is under that peculiar aspect that the main theme of this thesis is unveiled, which aims to analyze how the feelings of avulsion represented by the characters are featured: Camilo and Pedro Vicente, in the novels, respectively, O amor dos homens avulsos (2016), by Victor Heringer, and Terra Avulsa (2014), by Altair Martins. In order to achieve the proposed objective, it was investigated how the loss of tenderness and affectivity unfolds in emotional helplessness and, consequently, in sentimental avulsion, emphasizing the importance of the formation and breaking of affective bonds in the constitution of the subject's emotional structure. In addition, to examine the facets and development of depression, mourning and melancholy as feelings that cause the loneliness that plagues those characters and, finally, to profile avulsion as a characteristic feeling of contemporary malaise. Therefore, this research is anchored in the theory developed by Restrepo (1998), Bauman (1998; 2009), Pino (2003), Freud (2010) and Kehl (2015). Based on the results obtained through the analysis undertaken in this work, it is possible to highlight the consequences of sentimental and affective needs today, as well as the complexity that this time has instilled in the subjectivity of being and his/her incomprehension as a subject endowed with the capabilities of feeling.